Disability and the changing contexts of family and personal relationships - Ciciurkaite, Gabriele; Brown, Robyn Lewis (Emerald Publishing Limited, 2024)
The past 50 years have witnessed a transformation in the structure and function of families and households. The social and demographic catalysts for these changes - including but not limited to delayed marriage, the legalization of same-sex marriage, women's increased labor force participation, and declines in fertility and mortality - have further impacted norms around family life and the performance of formal and informal family roles. Despite these radical shifts, however, family and personal relationships are not well-represented in disability scholarship. In the interest of expanding disability scholarship on families, this volume of Research in Social Science and Disability brings together research and theoretical perspectives that challenge and revise dominant perspectives on disability and the changing contexts of family and personal relationships. Rooted in a sociological and anti-ableist understanding of families which recognizes that families are not only shaped by individuals and individual relationships, chapters instead concentrate on the social contexts in which families exist to shift our focus away from individuals and allows us to engage with the social structures and status hierarchies that may privilege or undermine families and relationships to varying degrees. Showcasing conceptually innovative work and cutting-edge methods related to the study of families, Disability and the Changing Contexts of Family and Personal Relationships presents not just a groundbreaking perspective on disability and family life, but also a new paradigm in disability scholarship.
Includes index.
Keywords: People with disabilities -- Family relationships.; Sociology of disability.; Social Science, People with Disabilities.; Relating to people with visible or hidden disabilities, impairments or conditions.; Disability: social aspects.; elektronické knihy; electronic books